Dietary fatty acids improve perceived sleep quality, stress, and health in migraine: a secondary analysis of a randomized controlled trial - Faurot, Keturah R.; Park, Jinyoung; Miller, Vanessa; Honvoh, Gilson; Domeniciello, Anthony; Mann, J. Douglas; Gaylord, Susan A.; Lynch, Chanee E.; Palsson, Olafur; Ramsden, Christopher E.; MacIntosh, Beth A.; Horowitz, Mark; et al. (Frontiers in Pain Research, 2023)
Background Migraine is a prevalent disabling condition often associated with comorbid physical and psychological symptoms that contribute to impaired quality of life and disability. Studies suggest that increasing dietary omega-3 fatty acid is associated with headache reduction, but less is known about the effects on quality of life in migraine. Methods After a 4-week run-in, 182 adults with 5–20 migraine days per month were randomized to one of the 3 arms for sixteen weeks. Dietary arms included: H3L6 (a high omega-3, low omega-6 diet), H3 (a high omega-3, an average omega-6 diet), or a control diet (average intakes of omega-3 and omega-6 fatty acids). Prespecified secondary endpoints included daily diary measures (stress perception, sleep quality, and perceived health), Patient-Reported Outcome Measurement Information System Version 1.0 ([PROMIS©) measures and the Migraine Disability Assessment (MIDAS). Analyses used linear mixed effects models to control for repeated measures. Results The H3L6 diet was associated with significant improvements in stress perception [adjusted mean difference (aMD): −1.5 (95% confidence interval: −1.7 to −1.2)], sleep quality [aMD: 0.2 (95% CI:0.1–0.2)], and perceived health [aMD: 0.2 (0.2–0.3)] compared to the control. Similarly, the H3 diet was associated with significant improvements in stress perception [aMD: −0.8 (−1.1 to −0.5)], sleep quality [aMD: 0.2 (0.1, 0.3)], and perceived health [aMD: 0.3 (0.2, 0.3)] compared to the control. MIDAS scores improved substantially in the intervention groups compared with the control (H3L6 aMD: −11.8 [−25.1, 1.5] and H3 aMD: −10.7 [−24.0, 2.7]). Among the PROMIS-29 assessments, the biggest impact was on pain interference [H3L6 MD: −1.8 (−4.4, 0.7) and H3 aMD: −3.2 (−5.9, −0.5)] and pain intensity [H3L6 MD: −0.6 (−1.3, 0.1) and H3 aMD: −0.6 (−1.4, 0.1)]. Discussion The diary measures, with their increased power, supported our hypothesis that symptoms associated with migraine attacks could be responsive to specific dietary fatty acid manipulations. Changes in the PROMIS© measures reflected improvements in non-headache pain as well as physical and psychological function, largely in the expected directions. These findings suggest that increasing omega-3 with or without decreasing omega-6 in the diet may represent a reasonable adjunctive approach to reducing symptoms associated with migraine attacks. Trial Registration: ClinicalTrials.gov NCT02012790.